Proceso atención de enfermería en paciente masculino de 79 años con insuficiencia cardiaca congestiva, Hospital General Alfredo Noboa Montenegro. - Taco Arias, Julio Cesar (2025)
Congestive heart failure is a clinical syndrome specialized in causing a set of cardinal symptoms (dyspnea, orthopnea, fatigue) and signs (jugular engorgement, third heart sound, peripheral edema), which are mostly caused by a structural alteration or function of the heart. The present study is applied to a 79-year-old male patient with a clinical picture of one week's evolution characterized by "cough with yellowish expectoration, dyspnea, anterior chest pain, edema in the lower limbs, orthopnea, asthenia and fatigue when walking or making any effort." The purpose of this clinical case study is to implement a nursing care process in a patient diagnosed with congestive heart failure in order to provide care in a rational, logical and systematic manner. The methods used for this practical-theoretical case study were through the clinical history, interview with the patient/family member, control and follow-up of the patient during his hospitalization. Likewise, to investigate more about this pathology, a meticulous research was carried out in scientific articles, scientific journals, books and web pages. Finally, a nursing assessment was carried out using Marjorie Gordon's functional patterns, in order to identify the patterns that were altered and provide optimal nursing care during her hospital stay, thus being able to meet the objectives proposed in this case study.